Affective styles and their association with anxiety and depression in a Japanese clinical sample. (28th January 2022) - Yamaguchi, Keiko; Ito, Masaya; Takebayashi, Yoshitake; Horikoshi, Masaru; Hofmann, Stefan G.
Abstract: Affective styles are assumed to play an important role in maintaining negative affect, including anxiety and depression. However, little is known about the longitudinal relationship between affective styles and symptoms. Therefore, we conducted a longitudinal study to examine the influence of affective styles, assessed using the Affective Style Questionnaire, on anxiety and depression among clinical populations in Japan. Using an online survey, 1521 participants (406 with major depressive disorder; 479 with one or more anxiety disorders; and 636 with both) answered the Affective Style Questionnaire and measures of emotion regulation, anxiety and depression symptoms. Data were collected twice over 2 months. Confirmatory factor analyses replicated the same four‐factor structure found in a previous sample of Japanese university students. Hierarchical regression analyses revealed that the affective styles had a slightly greater effect on anxiety symptoms but not on depression compared to other common emotion regulation strategies, such as suppression and reappraisal measured by the Emotion Regulation Questionnaire (ERQ). Limitations of this study were that it used online surveys, in which, participants' diagnostic statuses were based on unverifiable self‐reports. In conclusion, the association of affective styles with anxiety and depression among the clinical populations was prospectively confirmed. Further study is needed to examine the association considering the combination or profiles of affective styles among different emotional disorders.